Harnessing Technology Acceptance Model (TAM) on Information System to Safeguard Accelerated Data Collecting and Processing Amid COVID-19 Pandemic - Nofriani Nofriani; Moh. Fatichuddin (Jurnal Pekommas, 2022)
COVID-19 has penetrated every aspect of human civilization. BPS-Statistics Indonesia, a government institute responsible for conducting statistical surveys across the country, also faces challenges in the aftermath. COVID-19 forces social distancing, preventing data collectors from meeting the respondents in person and collecting data offline. The data collecting that uses printed questionnaires and the centralized data processing in BPS Headquarters Office causes delays in the whole process. The issue needs to be resolved using a reliable system that can fasten the entire procedure without printed questionnaires, decreasing person-to-person contact and decentralizing the data processing to users' ends. This research proposes and evaluates SIDUBES, an information system BPS-Statistics of Bengkulu Province, to collect data on large and medium manufacturing surveys by harnessing the Technology Acceptance Model (TAM). The model evaluates users' perception of Perceived Usability (P.U.), Perceived Helpfulness (P.H.), Perceived Assurance (P.A.), Viewpoint of Using (V.U.), and Continuity Intention (CI) in measuring the acceptance level. The results show that SIDUBES have met most of the users' requirements; V.U. and P.H. have a positive effect on CI; P.U. has a positive impact on P.A., and; P.A. has a positive effect on P.H.